Strengthening Waste Bank in Campus “BaSCamp” as Environmental Conservation Learning Device at STKIP PGRI Jombang - Kahan Tony Hendrawan; Umi Nur Qomariyah; Cahyo Tri Atmojo (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The increase of waste happened at schools and offices. The use of paper and plastic became the object of the waste increase in the environment. It also happened at STKIP PGRI Jombang. The effort in cleaning was only done in final disposal by the cleaning staff in campus and it was not managed maximally by recycling the waste. The service partner was Green Campus at STKIP PGRI Jombang as one of units of students’ activities that worked in environmental conservation. Green Campus had about 30 members of students from 6 departments. The concentration is on Green kampus STKIP PGRI Jombang to manage the bank waste held in January 2023. The problems of the partner are: (1) the waste bank needed training and accompaniment in managing and in organizing, (2) the lack of knowledge and skill of the organizers of the waste bank in implementing 3R (Reduce, Reuse, Recycle). The method used is Asset Based Community Driven Development approach where strengthening was done through education, training, and accompaniment to the understanding context and internalizing asset, potency, power and resource individually and maximally. The result of the community service is the same perception of the concept about waste bank held, the creation of waste bank management system with clear job description, improvement of knowledge in managing the waste in the process of 3 R in 80%.